ANALISIS MEDIA PEMBELAJARAN BAHASA INDONESIA ANAK BERKEBUTUHAN KHUSUS JENIS TUNARUNGU - Rahmawati Rahmawati; Idawati Idawati (Universitas Negeri Makassar, 2020)
Analysis of Learning Media for Children with Special Needs of the Deaf Type. This study studies describing the use of Indonesian language learning media for children with special needs as Deaf, and describing the interaction of the media used in learning Indonesian. This type of research is a qualitative descriptive study. The data in this study are the media in learning Indonesian language for Deaf children of class IX SMPLB-B YPPLB Makassar. The results showed that: the use of learning media for children with hearing impaired special needs in learning Indonesian in accordance with the characteristics of deaf children and the material to be discussed is the procedure text. Learning media, such as powerpoint media, whiteboard media, print media (loose sheets) and visual media that are not projected (pictures). While the use of these media is (1) activating students in learning, (2) students are responsive, (3) the media used are in accordance with the characteristics of Deaf children, and (4) achievement of learning goals that have not been maximized.